Regularities in the impurity element content of minerals during hydrothermal ore formation - Samusikov, V.P. (Russian geology and geophysics, 2010)
Many goldfields host scores of discovered gold ore occurrences with unclear prospects because of their insufficient geologic exploration. Since exploration is expensive, the occurrences should be first appraised by low-cost methods. Studying the typomorphic features of minerals from the goldfields of the Upper Yana–Kolyma region, we have established a relationship between the contents of isomorphic impurity elements (IIE) and the degree of solution supersaturation (DSS). Preliminary studies show that, based on this relationship, criteria can be developed for revealing “concealed” mineralogical–geochemical zonation and predicting mineralization to depth. The determining factor for the behavior of IIE, depending on the DSS, is their distribution coefficient ( K) with respect to the host element. If K > 1, the content of these elements decreases with increasing DSS during ore deposition; if K < 1, it increases. When a solution contains IIE with K > 1 and K < 1, they behave according to their distribution coefficients. In other words, when the DSS increases during ore deposition, IIE with K > 1 will be typical of early mineral segregations, and IIE with K < 1, of late ones. If the crystallization front migrates, this must give rise to a vertical zonation in the content of both groups of elements. The content of elements with K > 1 will decrease upsection, and that of elements with K < 1 will increase (“concealed” mineralogical–geochemical zonation). In connection with this subject, the paper reports data using native gold as an example. The behavior of Ag, Sb, Hg, Cu, Ni, and Co is discussed depending on the depth of deposit formation from the paleosurface (deep-seated → shallow); in the vertical section of individual deposits; depending on mineralization stages; in the cross-section of individual crystals with a zonal structure. The behavior of Ag, Sb, and Hg has been shown to be opposite to that of Cu, Ni, and Co in all these aspects. With respect to Au, the first group of elements has K < 1, and the second one, K > 1. Copper and antimony are of particular interest. In the vertical section of individual deposits, the Cu content of gold increases with depth and the Sb content decreases. The Cu/Sb ratio can be used to estimate the erosional truncation level of deposits and thus predict their extension to depth. Examples of well-explored deposits are given.